Healthcare professionals' perceptions of psychosocial support for family members in palliative care inpatient units-A qualitative descriptive study - Soikkeli-Jalonen, Anu; Mishina, Kaisa; Virtanen, Heli; Charalambous, Andreas; Haavisto, Elina (My University, 2022)
Aim: This study aimed to describe the psychosocial support healthcare profession-als in specialist palliative inpatient units provide to family members of palliative care patients.Design: A qualitative descriptive design.Method: The data were collected with focus group interviews and analysed with in-ductive content analysis.Results: Altogether, 48 healthcare professionals, including physicians, registered nurses and practical nurses, participated in the study. Information sharing was recog-nised as an essential element of support. Methods to improve support of family mem-bers included an opportunity to allocate recourses to the families, systematic support and strengthening healthcare professionals' competence in family care.The healthcare professionals describe their perceptions of psychosocial support for family members primarily through patient care and the patient's situation rather than family needs. Direct support for the family members is realised principally by informa-tion sharing and conversations. Healthcare professionals express their opportunities to implement support focusing on family members' needs restricted by reason of or-ganisational resources.The information can be used when developing and improving family care in pallia-tive care context to recognise the most relevant needs from healthcare profession-als' perspective and also when implementing healthcare professionals' education and training
Keywords: Families; Hospital; Interprofessional healthcare; Palliative care; Qualitative